Assessing the Influence of Shopee Advertising and Campaigns on Local Shoe Purchase Decisions - Refi Adi Herdiansyah; Anton Tirta Komara; Kadir Kadir; Haris Nurdiansyah (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2025)
This thesis addresses the growing trend of online shopping systems, highlighting the convenience offered by online shops through communication technology. The main problem under investigation is the factors influencing purchasing decisions in this digital marketplace. The research focuses on a shoe retail company, which utilizes online platforms such as Shopee for product sales. The primary objective of this study is to assess how advertising and campaigns impact purchasing decisions. The chosen methodology is a quantitative approach, carried out within the context of at a shoe retail company, allowing for an empirical analysis of these influences. The results reveal that advertising has a significant impact on purchasing decisions, while campaigns also contribute meaningfully. The findings indicate that these two variables collectively account for a substantial influence on purchasing decisions, with additional unexamined factors having a smaller impact. This research contributes novelty by providing insights into the specific influence of advertising and campaigns within an online marketplace context. The implications of these findings suggest that at a shoe retail company should focus on enhancing these variables to optimize their marketing strategies and improve purchasing decisions.